Using Robotics in the Learning of Computer Programming: Student Experiences Based on Experiential Learning Cycles - Reginald Gerald Govender; Desmond Wesley Govender (MDPI AG, 2023)
The understanding of basic constructs in computer programming has always been seen by students as challenging, especially for novice programmers with no prior exposure at the school level. This paper emanates from a larger study and sets out to explore the use of robotics to enhance the learning of computer programming by asking: what are students' experiences of using robotics when learning to program? Guided by Kolb's Experiential Learning Cycle, a series of workshops were conducted that promotes hands-on learning and encourages the use of tools in the learning process for knowledge development. The site for this study was a university campus in KwaZulu-Natal, South Africa. The sample was composed of 75 students, most of whom were first-year students who had just started a computer course and had no prior exposure to Computer Programming. The findings showed that the meaningful adoption of Kolb's experiential learning has proven to be successful in the progressional development of computer programming constructs when using a physical component such as a robot. The use of microcontrollers that provide a robotic element offering a physical attribute during the learning of code proves to be affective. It is hoped that the findings of this study will contribute to the development of innovative methods to introduce computer programming through the use of robotics.